#### Answer

(a) -1
(b) -21

#### Work Step by Step

We are given:
$f(x)=2x-3$ and $g(x)=4-x^2$
We evaluate:
(a) $f(f(2))=f(2*2-3)=f(1)=2*1-3=-1$
(b) $g(g(3))=g(4-3^{2})=g(4-9)=g(-5)=4-(-5)^{2}=-21$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(a) -1
(b) -21

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.